1998
DOI: 10.1097/00004728-199809000-00030
|View full text |Cite
|
Sign up to set email alerts
|

An Image-Processing System for Qualitative and Quantitative Volumetric Analysis of Brain Images

Abstract: In this work, we developed, implemented, and validated an image-processing system for qualitative and quantitative volumetric analysis of brain images. This system allows the visualization and quantitation of global and regional brain volumes. Global volumes were obtained via an automated adaptive Bayesian segmentation technique that labels the brain into white matter, gray matter, and cerebrospinal fluid. Absolute volumetric errors for these compartments ranged between 1 and 3% as indicated by phantom studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
225
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(229 citation statements)
references
References 32 publications
0
225
0
Order By: Relevance
“…At each center, scans were performed according to standardized protocols following the supervision of the MRI Reading Center (University of Pennsylvania) (Launer et al., 2015). Image processing, quality control checks, and automated brain tissue volume computations were performed at the MRI reading center, following previously described protocols (Goldszal et al., 1998; Lao et al., 2008; Launer et al., 2015; Shen & Davatzikos, 2002; Zacharaki, Kanterakis, Bryan, & Davatzikos, 2008). In brief, all imaging data were first converted to Neuroimaging Informatics Technology Initiative (NIFTI) format.…”
Section: Methodsmentioning
confidence: 99%
“…At each center, scans were performed according to standardized protocols following the supervision of the MRI Reading Center (University of Pennsylvania) (Launer et al., 2015). Image processing, quality control checks, and automated brain tissue volume computations were performed at the MRI reading center, following previously described protocols (Goldszal et al., 1998; Lao et al., 2008; Launer et al., 2015; Shen & Davatzikos, 2002; Zacharaki, Kanterakis, Bryan, & Davatzikos, 2008). In brief, all imaging data were first converted to Neuroimaging Informatics Technology Initiative (NIFTI) format.…”
Section: Methodsmentioning
confidence: 99%
“…As the first step of the process (see Fig. 2), an input brain image is preprocessed to remove skin, bone, fat, and other noncerebral tissues using a semiautomated software package developed by Christos Davatzikos and Jerry Miller at the Johns Hopkins University (Goldszal et al, 1998). Fig.…”
Section: Preprocessingmentioning
confidence: 99%
“…The number of methods proposed to address the brain segmentation problem reflects the importance of accurate and robust brain extraction. During the last 15 years, more than 20 brain extraction methods have been proposed using a variety of techniques, such as morphological operations (Goldszal et al, 1998;Lemieux et al, 1999;Mikheev et al, 2008;Park and Lee, 2009;Sandor and Leahy, 1997;Ward, 1999), atlas matching (Ashburner and Friston, 2000;Kapur et al, 1996), deformable surfaces (Dale et al, 1999;Smith, 2002), level sets (Baillard et al, 2001;Zhuang et al, 2006), histogram analysis (Shan et al, 2002), watershed (Hahn andPeitgen, 2000), graph cuts (Sadananthan et al, 2010), label fusion (Leung et al, 2011), and hybrid techniques (Carass et al, 2011;Iglesias et al, 2011;Rehm et al, 2004;Rex et al, 2004;Segonne et al, 2004;Shattuck et al, 2001). Studies evaluating these methods have found varying accuracy (Boesen et al, 2004;Fennema-Notestine et al, 2006;Hartley et al, 2006;Lee et al, 2003;Park and Lee, 2009;Shattuck et al, 2009).…”
Section: Introductionmentioning
confidence: 99%